Konsep Self Help Dalam Pendidikan Islam KH. Abdul Halim Majalengka - Nur Widad Mazaya; Nur Arifa; Ismail Marzuki Hasibuan; Ma'ruf Syifa'udin; Nur Arifa; Ismail Marzuki Hasibuan; Ma’ruf Syifaudin (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The community must be aware and wise in calculating a local leader who has a significant role in building and creating the history of a country. In an era when society tends to be static and fatalistic, Halim proposes dynamic and progressive thinking. By using historical research methods, this study found that Halim's quest to find national identity had been initiated since childhood until he died. Halim has contributed significantly to the growth of many other movements led by the younger generation since then. Halim also succeeded in solving local community problems, especially educational, da'wah and social problems. The emergence of the Islamic Community Association (PUI) organization is a fact of Halim's efforts and struggles. The purpose of this study was to determine the influence of Abdul Halim Majalengka in the world of education and Muslim society. The results of this study state that there is a movement from the work that has been done by Abdul Halim Majalengka. Keywords: KH. Abdul Halim, Thought, Islamic Education.